Book Review: Mezhevich, N. M., & Shimov, V. V. (2024). Belarus: Transformation and Modernization. Post-Soviet Development Results. Moscow: Institut Evropy RAN publ., 124 p. (In Russian) - Nadezhda G. Smolik (Vestnik RUDN. International Relations)
-